2008
DOI: 10.1080/15622970701310989
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers of brain-cell damage and C-reactive protein are unaffected by electroconvulsive therapy

Abstract: The effects of electroconvulsive therapy (ECT) on serum levels of the acute-phase reactant C-reactive protein (CRP) and intracellular enzymes such as alkaline phosphatase (ALP), lactate dehydrogenase (LDH), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and creatine kinase (CK), have received little attention. If brain cells are damaged, CK-BB, LDH and AST levels are expected to show (minor) elevations. We measured serum levels of prolactin, AST, ALT, LDH, ALP, CK and CRP before and 5 min, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…Furthermore, our finding that TNF-α levels did not change in response to ECT contrasted to the findings of Hestad et al (2003), where TNF-α was markedly raised in depressed patients compared to controls, and that clinical improvement with ECT correlated with a decline in TNF-α levels, with levels comparable to controls by the study’s end (Hestad et al, 2003). Finally, the present study did not detect any significant changes in CRP related to MDD or ECT, in keeping with one previous study (Giltay et al, 2008), but in contrast with several other reports of increased positive acute phase proteins such as CRP in patients with active and remitted MDD (Howren et al, 2009; Kling et al, 2007; O’Brien et al, 2006). …”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our finding that TNF-α levels did not change in response to ECT contrasted to the findings of Hestad et al (2003), where TNF-α was markedly raised in depressed patients compared to controls, and that clinical improvement with ECT correlated with a decline in TNF-α levels, with levels comparable to controls by the study’s end (Hestad et al, 2003). Finally, the present study did not detect any significant changes in CRP related to MDD or ECT, in keeping with one previous study (Giltay et al, 2008), but in contrast with several other reports of increased positive acute phase proteins such as CRP in patients with active and remitted MDD (Howren et al, 2009; Kling et al, 2007; O’Brien et al, 2006). …”
Section: Discussionsupporting
confidence: 92%
“…The acute increase of IL-6 following initiation of ECT has been demonstrated in previous studies. 20,21 However, two previous studies demonstrated no change in CRP during ECT 23,32 , which is surprising given the robust change observed in the current study, and the fact that IL-6 induces transcription of CRP. 33 …”
Section: Discussioncontrasting
confidence: 77%
“…In fact, markers of inflammation, for example, CRP, are also associated with depressive disorders [ 22 ]; however, the effects of ECT to acute phase reactants such as CRP and PCT are not well known yet. Giltay and colleagues reported an increase of PCT during ECT treatment, whereas CRP levels remained unchanged in their study [ 23 25 ]. Further, hyperhomocysteinemia has been associated with the development of certain somatic and psychiatric diseases, for example, major depressive disorder or dementia [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 97%